FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH UNTUK MENABUNG PADA PT. BNI (PERSERO) Tbk, CABANG USU MEDAN - Sagala, Roslinda (Jurnal Manajemen dan Bisnis, 2010)
PT. BNI (Persero) Tbk, USU Medan Branch is one of the government-owned enterprises. The bank collects funds from the public in the form of demand deposits, savings deposits, and channel it back in the form of credit. In this study, the authors focus on research for deposits. Number of clients who deposit funds in 2009-2010 has decreased. From the description formulated the research problem is "what is the most dominant factor influencing customers to save money on PT. BNI (Persero) Tbk, USU Medan Branch?" The purpose of this study was to determine and analyze the most dominant factor influencing customers to save money on PT. BNI (Persero) Tbk, USU Medan Branch. Benefits of the research is to provide material information to the leadership of the bank's most dominant factor influencing customers to save money. The study population was all clients are saving money on deposit with the PT. BNI (Persero) Tbk, USU Medan Branch in 2010. The samples taken as many as 125 people. Required data were collected through questionnaires and documentation techniques. Data analysis technique used was factor analysis. Based on the discussion, figures obtained by KMO Measure of Sampling Adeguacy (MSA) of 0.899 is above 0.50, with a significance of 0.000, then the appropriate variables for further analysis. Scree plot showing the chart, in which of the factor 1 to factor 2 (component source line number = 1 to 2), the line dropped sharply. Then from the number 2 to number 4, the direction of the line decreases with a smaller slope. The fifth factor was in the bottom of the Y-axis numbers (eigenvalues). This suggests that four factors best to summarize the twenty-five factors that influence the customer to save money. Before the rotation, the twenty-five variables that affect the customer to save money on PT. BNI (Persero) Tbk, USU Medan Branch is not clear where the factor a, then the necessary rotation. After rotation, the twenty-five variables are clearly factors which enter into. The dominant factor influencing customers to save money in the form of time deposits at PT. BNI (Persero) Tbk, USU Medan Branch with correlation values above 0.75 is the backlog of the correlation value of 0.782; deposit with a correlation value of 0.774; handling of customer complaints with correlation values of 0.756 and lucky draws with a correlation value of 0.751 . Of the four factors, the most dominant influence customers to save money is a backlog. Advice given to the leadership of the bank is better, the bank maintains customer order backlog increasing number of clients. To attract people to save in the form of deposits, the bank should increase the rates of time deposits, pay attention to the handling of customer complaints and increase the types of lottery.